Diet supplemented with African nutmeg (Monodora myristica) has antidepressant action in a rodent model of chronic unpredictable mild stress by regulating the vitamins, lymphocytes, platelets and immune organs - Ekeanyanwu Raphael Chukwuma; Chikezie Paul Chidoka; Bob Chile-Agada Adaeze (Scientific African, 2022)
Some of the problems associated with the current treatment protocol for depression include the negative perception associated with existing therapies for depression in some religions and beliefs, as well as negative impacts, a slow onset of therapeutic action, and the misuse of prescription, which may lead to suicidal attempts. The use of dietary therapy may offer a novel alternative approach to addressing these concerns. The study was carried out to determine whether including M. myristica (African nutmeg) seed in the diet lowers the risk of depression as well as leads to a change in some biochemical, haematological, and immunological parameter that arises in stressed animal models. Twenty male and female wistar rats were randomly assigned to four groups (n = 5); group I were stressed and fed alternative diet, group II were fed alternative diet only, group III were stressed and received African nutmeg diet while group IV were fed African nutmeg diet only. The fat, fibre and protein in African nutmeg were matched with corn oil, protein casein and a pure fibre source. Animal feed and stressors were administered once daily for five consecutive weeks from the 2nd week. Sucrose preference, open field, tail suspension and forced swim test were used to evaluate behavioural activity. In addition, biochemical parameters (serum protein, albumin, urea, creatinine, total and conjugated bilirubin, triglycerides, total cholesterol, HDL cholesterol, LDL cholesterol, vitamin B9 and vitamin B12), haematological parameters and immunological parameters, (Immune organ index and histology of thymus and spleen) were assessed. African nutmeg diet exhibited antidepressant-like action in the forced swim, open field, tail suspension and sucrose preference tests. Administration of the African nutmeg diet effectively increased the levels of lymphocytes, platelets, vitamin B9, vitamin B12 and immune function in chronically stressed rats. The findings serve as evidence that including African nutmeg (M. myristica) seed in the diet of rodents subjected to Chronic Unpredictable Mild Stress may reduce depression. Thus African nutmeg inclusion in the diet may serve as a dietary alternative in the management of depression at least in experimental animals.